CompTIA security+ certification study guide (exam SYO-301) - Clarke, Glen E. (McGraw-Hill, 2012)
Designed as the most comprehensive CompTIA Security+ self-study package, this Boxed Set includes CompTIA Security+ Certification Study Guide and CompTIA Security+ Certification Practice Exams, plus bonus CD-ROM content, at a discount of 12% off MSRP.